Re-Design of the Structure of the Batang I Industrial Flats Worker Building Using the Precast Concrete Method - Ridwan Riskyanto; Nasyiin Faqih; Suharto Suharto (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2023)
The Industrial Workers' Flats, located in the Batang Integrated Industrial Area, are supporting facilities workers use. The building was previously planned using conventional methods. In many cases, demands for fast and efficient construction work often occur, especially in the case of high-rise buildings. The need for multi-storey buildings encourages the need for an economical structural design that can be implemented quickly and efficiently without reducing the stiffness between the components of the building structure. From the explanation above, it is re-planned using the precast concrete method so that the work is neat, precise, and fast. In this planning, the SRPMK system is used. It needs good supervision in precast concrete, especially in joints, because precast joints are not as monolithic as conventional ones. It is necessary to develop precast technology to be more innovative in its use and easier to apply.